Understanding unfolding and refolding of the antibody fragment (Fab). I. In-vitro study - Gani, Kayanat; Bhambure, Rahul; Deulgaonkar, Prashant; Mehta, Deepa; Kamble, Manoj (Biochemical Engineering Journal, 2020)
In-vitro protein refolding is a major rate-limiting step in the large scale production of antibody fragments expressed using a microbial source like E. coli. This investigation is focused on understanding the in-vitro unfolding and refolding of the multi-domain protein involving inter-domain disulfide linkage, like antibody fragment (Fab). Solubilization behavior of the inclusion bodies and unfolding events of Fab fragment (Biosimilar rHu Ranibizumab) were studied using nano-differential scanning fluorimetry (nano-DSF). Fab unfolding behavior was studied by fitting experimental data with the two-state and three-state thermodynamic model. Based on the Fab unfolding understanding, a two-stage design of experiment (DoE) strategy was used for the optimization of the in-vitro refolding condition of a Fab fragment. Refolding yield of 56.03 +/- 1.15 % was achieved using the optimized oxidative refolding conditions maintained by appropriate dilution factor and redox reagent ratio. Refolding kinetics of the rHu Ranibizumab was analyzed using a three-parameter kinetic model showing rate constant k(1) :7.05e(-6) l/mg.min, k(2) :0.57 l/mg.min, and k(3) :310.19 l/mg.min. Based on observed refolding kinetics, it was concluded that the Fab refolding follows a three-state mechanism with the refolding intermediate/(s) formation from light and heavy chain of the Fab fragment as an overall rate-limiting step. The method described here is a useful tool to identify high-yield scalable refolding conditions for multi-domain proteins involving inter-domain disulfide bonds.
Keywords: Antibody fragment; In-vitro refolding; Refolding kinetics; rHu Ranibizumab; Two-state and Three-state models

Cloning and expression of antibody fragment (Fab) I: effect of expression construct and induction strategies on light and heavy chain gene expression - Mehta, Deepa; Chirmade, Tejas; Tungekar, Aatir A.; Gani, Kayanat; Bhambure, Rahul (Biochemical Engineering Journal, 2021)
Dual promoter expression constructs offer time and cost-effective alternatives to produce multi-domain proteins like antibody fragments. This investigation is focused on understanding the effect of expression construct (dual promoter vs. co-transformation strategy), codon optimization, and induction strategies on yield and expression stoichiometry of LC and HC genes of antibody fragment at shake-flask and bioreactor scale. rHu biosimilar Ranibizumab was selected as a model protein for the study. Expression stoichiometry of HC and LC gene at mRNA level was studied using RTqPCR, whereas protein expression level was studied quantitatively using RP-HPLC and SDS-PAGE analysis. In the case of dual promoter expression construct, it was observed that LC gene cloned in the MCS1 of the duet vectors has > 2-fold expression than the HC gene, cloned in the MCS2. Transcript abundance profile of the HC and LC genes determined at different time intervals post-induction shows a difference in the gene expression at the transcriptional level. Comparative analysis of dual promoter and co-transformation strategy shows better stoichiometry in co-transformation (1:1.3), whereas higher protein yield in a dual expression system (>2.4 fold). The use of lactose and galactose as inducers show higher Fab yield of 2.30 +/- 0.03 g/L and 2.81 +/- 0.06 g/L with expression stoichiometry of 1:1.9 and 1:2 (HC: LC) respectively than IPTG-based induction with a protein yield of 1.40 +/- 0.02 g/L.
Keywords: Dual promoter vector; Expression stoichiometry; High cell density fermentation; rHu biosimilar Ranibizumab; Transcript abundance

Dimerization of SARS-CoV-2 nucleocapsid protein affects sensitivity of ELISA based diagnostics of COVID-19 - Khan, Wajihul; Khan, Nida; Mishra, Avinash; Gupta, Surbhi; Bansode, Vikrant; Mehta, Deepa; Bhambure, Rahul; Rathore, Anurag (International Journal of Biological Macromolecules, 2022)
Nucleocapsid protein (N protein) is the primary antigen of the virus for development of sensitive diagnostic assays of COVID-19. In this paper, we demonstrate the significant impact of dimerization of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) N-protein on sensitivity of enzyme-linked immunosorbent assay (ELISA) based diagnostics. The expressed purified protein from E. coli is composed of dimeric and monomeric forms, which have been further characterized using biophysical and immunological techniques. Indirect ELISA indicated elevated susceptibility of the dimeric form of the nucleocapsid protein for identification of protein-specific monoclonal antibody as compared to the monomeric form. This finding also confirmed with the modelled structure of monomeric and dimeric nucleocapsid protein via HHPred software and its solvent accessible surface area, which indicates higher stability and antigenicity of the dimeric type as compared to the monomeric form. The sensitivity and specificity of the ELISA at 95% CI are 99.0% (94.5-99.9) and 95.0% (83.0-99.4), respectively, for the highest purified dimeric form of the N protein. As a result, using the highest purified dimeric form will improve the sensitivity of the current nucleocapsid-dependent ELISA for COVID-19 diagnosis, and manufacturers should monitor and maintain the monomer-dimer composition for accurate and robust diagnostics.

Cloning and expression of antibody fragment (Fab) II: Effect of expression hosts on light and heavy chain gene expression - Mehta, Deepa; Chirmade, Tejas; Nainwal, Neeraj; Bhambure, Rahul (Biochemical Engineering Journal, 2023)
Protein expression stoichiometry of individual subunits plays a critical role in the formation of multi-domain functional therapeutic proteins like antibody fragments. In this study, we have evaluated light to heavy chain ratio (LC: HC) of rHu Ranibizumab expressed using duet expression vector in six E. coli strains. The LC: HC ratio at the protein level was determined using RP-HPLC whereas transcript abundance of LC and HC at the mRNA level was determined using RTqPCR. Protein level study as well as the transcript abundance profiles of the LC and HC genes were observed to be differentially expressed across the E. coli strains. BL21 STAR (DE3) and Origami 2 strains resulted in a nearly equal expression ratio of LC and HC genes. Untargeted shotgun proteomics analysis was performed to identify the differentially expressed proteins. Total 1083 proteins were identified in the spectral IDA library, while 244 and 149 proteins were differentially expressed in Origami 2 and BL21 STAR (DE3) respectively. These proteins are associated with translation and nucleotide biosynthesis pathways. Ob-tained results provide insights into the impact of different E.coli host strains on LC: HC ratio, the probable reasons behind the unbalanced gene ratio, and provide useful transcriptomic and proteomics analysis protocols.
Keywords: E.coli host strains; Expression stoichiometry; Proteome analysis; rHu biosimilar Ranibizumab; Transcript abundance